2000
DOI: 10.1021/jp001161s
|View full text |Cite
|
Sign up to set email alerts
|

Products of the Gas-Phase Reactions of OH Radicals with p-Xylene and 1,2,3- and 1,2,4-Trimethylbenzene: Effect of NO2 Concentration

Abstract: Products of the gas-phase reactions of the OH radical with p-xylene and 1,2,3-and 1,2,4-trimethylbenzene have been measured by gas chromatography in the presence of varying concentrations of NO 2 . Our product analyses show that the ring-cleavage products 2,3-butanedione (from 1,2,3-and 1,2,4-trimethylbenzene) and 3-hexene-2,5-dione (from p-xylene and 1,2,4-trimethylbenzene) exhibit a dependence of their formation yields on the NO 2 concentration, with higher yields from the reactions of the OH-aromatic adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 47 publications
(137 reference statements)
8
83
0
Order By: Relevance
“…Also consistent with previous experimental results [3,29], the reaction of IM3 with nitrogen oxide under the presence of NO is predicted to occur via two pathways by our calculations. One pathway is unimolecular decomposition via TS2 involving O 1 AO 2 cleavage.…”
Section: Peroxyl Radicalssupporting
confidence: 92%
See 1 more Smart Citation
“…Also consistent with previous experimental results [3,29], the reaction of IM3 with nitrogen oxide under the presence of NO is predicted to occur via two pathways by our calculations. One pathway is unimolecular decomposition via TS2 involving O 1 AO 2 cleavage.…”
Section: Peroxyl Radicalssupporting
confidence: 92%
“…Partially due to the complicacy of VOCs species, therefore the compositions of SOA formed from VOCs, and the difficulty in direct measurements of the highly reactive intermediates during the oxidation reaction [27,28], experimental ratification of the entire reaction course has not yet obtained [1,3,10,29,30]. Previous studies showed that in the presence of OH radical the main reaction path is OH addition to the aromatic ring to form a xylene-OH adduct (consuming $90% of OH radicals) with Habstraction from one methyl group to form a methylbenzyl radical (consuming $10% of OH radicals) being the minor route [18,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Atkinson and Aschmann (1994) observed a decrease of the yield of 2,3-butanedione from o-xylene with the expected curvature and a [NO 2 ] 1/2 value of about 2 ppm, confirmed by an experiment with fivefold decreased level of O 2 (RO 2 from the equilibrium (7/-7), see Volkamer et al (2002b). The decreasing yields of 2,3-butanedione from 1,2,3-trimethylbenzene and 1,2,4-trimethylbenzene with increasing NO 2 observed by Bethel et al (2000) can be taken as a hint at a similar competition of NO 2 with O 2 in the reaction with the OHadducts.…”
Section: Smog Chamber Experiments and Product Studiesmentioning
confidence: 93%
“…While tropospheric NO 2 levels (averaged over the region of benzene oxidation) are much lower than the 1.3 ppm value calculated for benzene, scavenging by NO 2 becomes important in high-NO x chamber experiments. Klotz et al (2002) to deliver 6% of phenol from benzene), Bethel et al (2000, yields of 3-hexene-2,5-dione from p-xylene), and Berndt and Böge (2003, yields of catechol from phenol decreasing from 73% in the absence to 35% at high NO 2 ), respectively. The agreement is excellent, except for phenol, where the chamber data imply a fivefold higher efficiency of NO 2 .…”
Section: Smog Chamber Experiments and Product Studiesmentioning
confidence: 99%
See 1 more Smart Citation